A review of stock-recruitment relationships with reference to flatfish populations - Iles, T.C. (Netherlands journal of sea research, 1994)
The relationship between stock and recruitment in fish populations has been a subject of many studies and some controversy, even to the extent that it has been questioned whether the two can be related in any meanignful way. The denial of a meaningful stock-recruitment relationship has profound and disturbing influences on the science of fish population dynamics and would seem to be something of a policy of despair. A more constructive approach is to acknowledge the difficulties in establishing a stock-recruitment relationship from the available information but still to seek the best interpretation of the data for the purposes for which the analysis is intended. Among the models that have been developed to fit stock-recruitment curves to data sets are the well-known Beverton-Holt and Ricker curves, both of which have two parameters. Less commonly used is the two-parameter model of Cushing. These two-parameter models have been generalized to give three-parameter models whose shape can be varied by settings of the parameters so as to model a wide range of observed stock-recruitment curves. In this paper these models and their underlying assumptions are described. Statistical methods of fitting the curves to data are reviewed with emphasis on the appraisal of the fitted curve, concentrating on the use for which the fitted curve is intended. Methods of choosing between different curves are discussed. The review is illustrated with examples of stock-recruitment data derived for various flatfish stocks. Among the questions that are discussed is whether there are any features of stock-recruitment relationships for flatfish that differentiate them from those of other species. Methods for testing the null hypotheses that there is no relationship between stock and recruitment and that recruitment in flatfish is not influenced by environmental or other biological factors are described. Of the 20 flatfish stocks for which suitable stock and recruitment data are available, it is shown that in six cases there is a statistically significant relationship between stock size and recruitment. In one of these cases the relationship is significantly strengthened by the incorporation of an environmental measurement. Of the six significant stock-recruitment relationships one is strongly domed and three are the right-hand arm of a domed curve. In the other two cases average recruitment increases with increasing stock size, but it is not possible to differentiate between a domed and an asymptotic curve. This evidence of density-dependence in the stock-recruitment relationships for flatfish is further strengthened by an examination of those cases in which the model of constant recruitment, independent of stock size, is not rejected. In eight of these stocks it is shown that the model of constant recruitment is favoured in preference to a model in which recruitment is directly proportional to stock size. Although recruitment may vary about a constant average level over a restricted range of stock size, it is not biologically possible for a population to sustain a high level of recruitment at low stock sizes. Thus in these eight cases there is further evidence of an underlying, but as yet unidentified, stock-recruitment relationship.